Impact of nonionizing electromagnetic radiation on male infertility: an assessment of the mechanism and consequences. (3rd June 2022) - Gautam, Rohit; Priyadarshini, Eepsita; Nirala, JayPrakash; Rajamani, Paulraj
Abstract: Purpose: Environment and lifestyle factors are being attributed toward increased instances of male infertility. Rapid technological advancement, results in emission of electromagnetic radiations of different frequency which impacts human both biologically as well as genetically. Devices like cell phone, power line and monitors emit electromagnetic radiation and are a major source of the exposure. Numerous studies describe the detrimental consequence of radiation on physiological parameters of male reproductive system including sperm parameters (morphology, motility, and viability), metabolism and genomic instability. While the thermal and nonthermal interaction of nonionizing radiations with biological tissues can't be ruled out, most studies emphasize the generation of reactive oxygen species. Oxidative stress alters redox equilibrium and disrupts morphology and normal functioning of sperms along with declination of total anti-oxidant capacity. Conclusion: In this paper, we describe a detailed literature review with the intent of analyzing the impact of electromagnetic radiation and understand the consequence on male reproductive system. The underlying mechanism suggesting ROS generation and pathway of action has also been discussed. Additionally, the safety measures while using electronic gadgets and mobile phones has also been presented.